The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ijms222413214
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Inhibition of Sonic Hedgehog Signaling Suppresses Tumor Development in a Murine Model of Intrahepatic Cholangiocarcinoma

Abstract: Cholangiocarcinoma (CCC) is the second most primary liver cancer with an aggressive biological behavior, and its incidence increases steadily. An aberrant up-regulation of the sonic hedgehog signaling pathway has been reported in a variety of hepatic diseases including hepatic inflammation, fibrosis, as well as cancer. In this study, we determined the effect of a sonic hedgehog inhibitor, vismodegib, on the development of CCC. Through database analyses, we found sonic hedgehog signaling was up-regulated in hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Aberrant activation of the Hh signaling pathway has been shown to positively regulate tumorigenesis in human cancers, including CCA 42,43 . Inhibitors of the Hh pathway also been reported to suppress the development of CCA 44 . After collecting the supernatant from CCA cells and exploring the changes in its composition using a cytokine array, we observed that the regulation of CCL2 by EHF was particularly significant.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Aberrant activation of the Hh signaling pathway has been shown to positively regulate tumorigenesis in human cancers, including CCA 42,43 . Inhibitors of the Hh pathway also been reported to suppress the development of CCA 44 . After collecting the supernatant from CCA cells and exploring the changes in its composition using a cytokine array, we observed that the regulation of CCL2 by EHF was particularly significant.…”
Section: Discussionmentioning
confidence: 83%
“… 42 , 43 Inhibitors of the Hh pathway also been reported to suppress the development of CCA. 44 After collecting the supernatant from CCA cells and exploring the changes in its composition using a cytokine array, we observed that the regulation of CCL2 by EHF was particularly significant. CCL2, also known as MCP‐1, recruits macrophages from the bloodstream to the microenvironment by binding to CCR2 on the macrophages.…”
Section: Discussionmentioning
confidence: 98%
“…Itraconazole in cholangiocarcinoma: 5-LO and its leukotriene products contribute to the growth of cholangiocarcinoma [207][208][209]. Hh signaling is a core growth-driving element in cholangiocarcinoma, and prominently so in the stem subset [210][211][212][213][214][215]. 5-LO is one of the drivers of both myeloid-derived suppressor cell immunosuppression and stemness in cholangiocarcinoma [216].…”
Section: Itraconazolementioning
confidence: 99%